Integrating technological pedagogical content knowledge in Learning: A systematic review - Arifuddin Arifuddin; Siti Khoiriyah; Hendi Sugianto; Abdul Rahim Karim (Universitas Papua, 2025)
The use of technology in educational contexts has experienced rapid growth in recent years. This breakthrough offers great potential to improve the quality of learning and teaching at various levels of education. One approach that dominates the conversation is the integration of technological pedagogical content knowledge (TPACK) in learning, which includes the alignment of three main components, namely technology (T), pedagogy (P), and content knowledge (CK). This study uses a systematic literature review approach to collect, select, and determine articles, then analyze and synthesize the latest research findings on the integration of TPACK in learning to improve teacher professionalism. The results showed that the trend of research studies related to TPACK in 2019 to 2023 discussed several components such as self-efficacy, a complete understanding of the dimensions of TPACK, the ability to analyze challenges and obstacles in the use of technology in learning, the ability to collaborate in the digital era, and the ability to build a positive paradigm in integrating technology in the learning process.